Understanding Scenario of Casteism in Twentieth Century India through Satyajit Ray Film Sadgati (Global Journal of Human-Social Science, 2022)
This article tries to emphasis the actual scenario of Casteism in twentieth century of India solely on the basis of Satyajit Ray s film Sadgati 1981 Although this article doesn t focus on film theories and criticism of Sadgati as a film but on sociological aspect of castesim in India Sadgati is a Hindi movie but in this article the dialogues of the movie as per requirement is translated by author
Keywords: casteism; sadgati; satyajit ray; film